2014
DOI: 10.1016/j.pjnns.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for re-bleeding of aneurysmal subarachnoid hemorrhage: Meta-analysis of observational studies

Abstract: Sex, high SBP, high Fisher grade, aneurysm size larger than 10mm, and poor clinical condition were independent risk factors for aneurysmal re-bleeding. The importance of early aneurysm intervention and careful consideration of patient risk factors should be emphasized to eliminate the risk of re-bleeding and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Preoperative aneurysm rebleeding has traditionally been a significant reason contributing to morbidity and mortality after aSAH. Previously identified risk factors for preoperative rebleeding have included sex, systolic blood pressure > 160 mm Hg, high Fisher grade, aneurysm characteristics (location, size, and numbers), hyperglycemia, neurological severity ( 5 9 , 11 13 , 25 29 ). Rebleeding following aSAH is a complex and multifactorial event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative aneurysm rebleeding has traditionally been a significant reason contributing to morbidity and mortality after aSAH. Previously identified risk factors for preoperative rebleeding have included sex, systolic blood pressure > 160 mm Hg, high Fisher grade, aneurysm characteristics (location, size, and numbers), hyperglycemia, neurological severity ( 5 9 , 11 13 , 25 29 ). Rebleeding following aSAH is a complex and multifactorial event.…”
Section: Discussionmentioning
confidence: 99%
“…The major early complication is aneurysmal rebleeding with an incidence of 4-13.6% during the first 24 h (3,4). Early rebleeding is associated with poor-neurosurgical outcomes and mortality rates as high as 50-80% (3,5). Some studies identified risk factors for preoperative rebleeding have included sex, advanced age, systolic blood pressure >160 mmHg, aneurysm size larger than 10 mm, neurological severity (high Fisher grade and high Hunt-Hess grade), and biomarkers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6, as a kind of glycoprotein, can participate in the collective inflammatory response and anti-infective defense mechanisms ( 13 , 14 ). At present, it is recognized that IL-6 is a kind of multi-functional glycoprotein cell inflammatory factor involved in various inflammatory reactions of central nervous system, which can cause immune response to the brain tissue damage and inflammation ( 15 ). CRP can be synthesized after IL-6 induction, thus activating the body's complement system and improving the immunity ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…DA has a worse clinical outcome, with higher risk of rupture with than SA [5][6][7]. A diameter greater than 10 mm is an independent risk factor for re-bleeding of an aneurysm [8]. The preferred treatment options of DA are vessel occlusion, surgical trapping, or flow diverter [9], whereas clipping or stenting is more frequently used for SA.…”
Section: Introductionmentioning
confidence: 99%